2023
DOI: 10.15252/emmm.202216805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cognitive signatures of ageing partially restored through synthetic delivery of IL2 to the brain

Abstract: Cognitive decline is a common pathological outcome during aging, with an ill-defined cellular or molecular basis. Among the cellular changes observed with age are alterations to neuronal plasticity, changes in the glial compartment and the decline of the neurogenic niche.In the recent years, the concept of inflammaging, defined as a low-grade inflammation increasing with age, has emerged as a nexus for age-related diseases. This increase of basal inflammation is also observed in the central nervous system. Whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…Aging is characterized by a low-grade chronic inflammation, and a marked gliosis in different areas of the CNS including the brain. Recent work showed that local expansion of Treg in the brain through interleukin-2 overexpression reverses molecular and cognitive signatures of aging such as gliosis, inflammation, and cognitive decline(Lemaitre et al 2023). Similar to what has already been described in the brain, disruption of retinal immune regulation is a key contributor to the development of age-related diseases(Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Aging is characterized by a low-grade chronic inflammation, and a marked gliosis in different areas of the CNS including the brain. Recent work showed that local expansion of Treg in the brain through interleukin-2 overexpression reverses molecular and cognitive signatures of aging such as gliosis, inflammation, and cognitive decline(Lemaitre et al 2023). Similar to what has already been described in the brain, disruption of retinal immune regulation is a key contributor to the development of age-related diseases(Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analyses have revealed that during physiological conditions, microglia have a “resting” transcriptomic profile, which is characterized by greater expression of genes that contribute to CNS maintenance. In contrast, in models of neurodegeneration, inflammation, and ageing, microglia are thought to favor the expression of inflammatory markers, thus triggering a gradient of microglial activation [ 68 , 69 , 70 ]. For example, in a study using mice treated with lipopolysaccharide (LPS) in early life, it was possible to observe a series of alterations in microglial gene expression that favored the development of depressive-like behaviors in adolescence [ 71 ].…”
Section: Neuroinflammation: Function Of Glial Cellsmentioning
confidence: 99%
“…Under these circumstances, the expression of homeostatic markers is decreased, while the expression of genes related to pro-inflammatory mechanisms is enhanced. Interestingly, these changes appear to be dependent on the brain region where these cells are located [ 70 , 114 ]. Interestingly, transcriptome analysis indicated that the induction of inflammatory gene expression in astrocytes is dependent on the Orai1 calcium channel, since genetic inhibition of this channel prevented this induction.…”
Section: Neuroinflammation: Function Of Glial Cellsmentioning
confidence: 99%
“…This involves eliminating neuroimmunogens, polarizing microglia, modulating astrocytes, and restoring normal neuronal function [9,10]. Furthermore, interventions aimed at enhancing astrocyte-mediated IL-2 production to expand local Treg populations in the CNS have shown promise in mitigating inflammatory damage and facilitating repair in mouse models of traumatic brain injury, stroke, multiple sclerosis and ageassociated cognitive decline [11,12].…”
Section: Introductionmentioning
confidence: 99%